2,4-Dimethoxybenzyl Group for the Protection of Tetrazole: An Efficient Synthesis of Olmesartan Medoxomil through C–H Arylation - Seki, Masahiko (Synthesis, 2015)
The 2,4-dimethoxybenzyl (DMB) group was found to be effective for protecting tetrazoles. The DMB group is inert to various conditions, including those for ruthenium-catalyzed C–H arylation, but is readily cleaved under mild conditions. The use of a DMB protecting group permitted a synthesis of highly functionalized olmesartan medoxomil in a few steps.
Keywords: protecting groups; arylations; heterocycles; biaryls; drugs; tetrazoles